Differences in Serum Creatinine Levels in Controlled and Uncontrolled Type 2 Diabetes Mellitus Patients - Esya Yuliana; Angki Purwanti; Tri Presetyorini (CV. CENDIKIA JENIUS INDONESIA, 2024)
Diabetes Mellitus is in the top 10 causes of death in the world. Indonesia ranks 5th out of 10 countries in the number of diabetes mellitus sufferers in adults aged 20-79 years. Type 2 Diabetes Mellitus is the most common type of Diabetes Mellitus. Examination of the HbA1c value is the gold standard examination for Type 2 Diabetes Mellitus. In PERKENI 2021, the risk of suffering from Type 2 Diabetes Mellitus increases with increasing age and it is recommended to screen for Type 2 Diabetes Mellitus at the age of > 40 years. The second most common complication of Diabetes Mellitus in Indonesia is nephropathy. Diabetic nephropathy is the main cause of end-stage renal failure which is the 5th stage of chronic renal failure. Examination of creatinine in the blood is an important parameter to determine kidney function. The aim of this study was to determine the average difference between serum creatinine levels in controlled and uncontrolled type 2 diabetes mellitus. This research was an analytical observational study with a cross-sectional design using secondary data from Type 2 Diabetes Mellitus sufferers without Chronic Kidney Failure from medical records at Hospital X in Jakarta in January-December 2023. The research data consisted of 368 respondents. The result was p-value = 0.688. The conclusion of this study is that there is no difference in mean between serum creatinine levels in controlled and uncontrolled Type 2 Diabetes Mellitus sufferers. Furthermore, research can be carried out using respondents with a duration of Diabetes Mellitus ≥ 10 year.